Multiprotease supplementation in laying hen diets: Impact on performance, egg quality, digestibility, gut histomorphology, and sustainability - Elijah Ogola Oketch; Myunghwan Yu; Shan Randima Nawarathne; Nuwan Chamara Chaturanga; Venuste Maniraguha; Bernadette Gerpacio Sta.Cruz; Eunsoo Seo; Jeseok Lee; Haeeun Park; Hans Lee; Jung Min Heo (Poultry Science)
Laying hen responses to supplemental multiprotease on performance, egg quality, digestibility, gut histomorphology, nitrogen excretion, and economic performance of laying hens until 37 weeks of age were investigated. A total of 189 25-week-old Hy-Line Brown hens were housed in enriched cages (7 birds/cage) and randomly allocated to 1 of 3 diets with 9 replicates per treatment. Dietary treatments included: an adequate positive control- PC [met the breed and age standards for crude protein (CP) and amino acids (AA)]; negative control- NC (90 % CP and AA requirement); and NC supplemented with multiprotease – NCMP. Multiprotease was supplemented at 300 g/t of feed equating to 2400 U/kg. Egg production rate and feed intake were not altered (P > 0.10) by the dietary treatments. Between 25 and 37 weeks of age (woa), the NCMP diet reduced the feed conversion ratios by 3 % (1.91 vs 1.97; P < 0.05) in comparison to the NC diet while improving (P < 0.05) the egg weights by 3 % (58.56 vs 56.68); Haugh units by 2 % (91.78 vs 90.20); and breaking strength by 1 % (4.65 vs 4.61). Marginally intensified yolk color and albumen height (P < 0.10) were also observed with the NCMP diet. Furthermore, the NCMP diet marginally improved the villus height, width, and absorptive surface area (P < 0.10) relative to NC. Multiprotease-supplemented NCMP diet improved (P < 0.05) the digestibility of crude protein; and amino acids including lysine, methionine, phenylalanine, isoleucine, leucine, glutamine, tyrosine, relative to the NC diet. Lowered AA/CP diets (NC and NCMP) reduced the N excreted and feed costs (P < 0.05) relative to the PC diet. Multiprotease increased the returns on investment (P < 0.10), and nitrogen retained in egg (P < 0.05) from 25- 37woa. Conclusively, feeding reduced CP/AA diets maintained the egg production rate while reducing the N excreted and feed costs. Multiprotease modulation of ileal absorptive capacity and nutrient digestibility is linked to improved feed efficiency, egg quality, and revenue estimates of supplemented hens.